2011
DOI: 10.3126/ajms.v1i2.3199
|View full text |Cite
|
Sign up to set email alerts
|

Placental Lead and its Interaction with Some Essential Metals among Women from Lucknow, India

Abstract: Objective: The placenta connects and separates two genetically distinct individuals: the mother and the fetus. There is no placental-fetal barrier blocking lead transport, placing the fetus at high risk from lead exposure. The placenta has been investigated as a possible indicator of environmental exposures. Recent studies have been focused on the interaction between toxic and essential metals in placenta as there is little information on the levels of lead and essential metals in human placental tissue in Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Information on laboratory quality controls differed between the earliest and the more recent papers: Before the year 2000, only 11 studies (26.8%) specified having internal quality controls and 6 studies (14.6%) mentioned external controls. In contrast, all studies published after 2000 except 1 ( Terrones-Saldivar et al 2008 ) reported the use of standardized quality control procedures that generally comprised evaluation of accuracy and precision by analysis of certified reference material, and 2 studies included additional interlaboratory comparisons ( Singh et al 2010 ; Zagrodzki et al 2003 ). Only half of the studies specified the limit of detection (LOD), merely stating the value or including the procedure used to treat values below it.…”
Section: Resultsmentioning
confidence: 99%
“…Information on laboratory quality controls differed between the earliest and the more recent papers: Before the year 2000, only 11 studies (26.8%) specified having internal quality controls and 6 studies (14.6%) mentioned external controls. In contrast, all studies published after 2000 except 1 ( Terrones-Saldivar et al 2008 ) reported the use of standardized quality control procedures that generally comprised evaluation of accuracy and precision by analysis of certified reference material, and 2 studies included additional interlaboratory comparisons ( Singh et al 2010 ; Zagrodzki et al 2003 ). Only half of the studies specified the limit of detection (LOD), merely stating the value or including the procedure used to treat values below it.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a quality check sample was always run with each set of samples for lead analysis to maintain accuracy. 14 Placental level of metals (Pb, Cd, Fe, Zn and Cu) were analysed by ICP-MS (Inductive Coupled Plasma-Mass Spectrophotometer) (Element XR, thermo Fisher Scientific, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The strong band appearing at 1665 cm -1 is fairly assigned to ν(C=O) stretching of semicarbazone [23]. In the IR spectra of complexes of NBPS this band undergoes negative shift and appears at 1640 cm -1 which is indicative of its coordination to the metal ions through oxygen [24,25]. The medium band appearing at 1630 cm -1 in the IR spectra of free ligand is attributed to ν(C=N) of azomethine group of the ligand [26].…”
Section: Resultsmentioning
confidence: 99%